2015
DOI: 10.1016/j.micres.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and diversity of bacterioplankton communities in subtropical seawater around Xiamen Island, China

Abstract: Marine bacterioplankton communities have profound impact on global biogeochemical cycles and ecological balances. However, relatively little is known about the bacterioplankton communities and the factors shaping their spatial distribution in subtropical island. Here, the bacterioplankton communities around a typical subtropical island, Xiamen Island, were revealed by analyzing bacterial 16S rRNA gene through quantitative PCR (qPCR) and 454 pyrosequencing methods. The qPCR results indicated that the abundance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…In general, the prevalence of specific viral populations follows that of their hosts. The composition of the metavirome sequenced in the current study is consistent with the results of 16S rRNA gene analysis performed on samples from the same habitat [ 32 ]. The most dominant bacterial phylum was Proteobacteria , followed by Bacteroidetes , which is consistent with our assignment of the virome.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In general, the prevalence of specific viral populations follows that of their hosts. The composition of the metavirome sequenced in the current study is consistent with the results of 16S rRNA gene analysis performed on samples from the same habitat [ 32 ]. The most dominant bacterial phylum was Proteobacteria , followed by Bacteroidetes , which is consistent with our assignment of the virome.…”
Section: Discussionsupporting
confidence: 85%
“…The Jiulong River estuary (JRE) is a typical subtropical macro-tide estuary connected with Xiamen Sea harbor and on the southwest coast of the Taiwan Strait. A recently published study that investigated the distribution and diversity of bacterioplankton communities of Xiamen Sea harbor found that the sampling site near the JRE exhibited the highest bacterial diversity, and was significantly influenced by total nitrogen and total phosphorus [ 32 ]. Because of the nature of the host-specific interactions, we could expect the composition of viruses (most of which are phages) to follow that of the bacterial community.…”
Section: Introductionmentioning
confidence: 99%
“…The OTU richness and Shannon index were significantly negatively correlated with AN. However, in other studies of similar environments, higher richness was often observed in coastal rather than offshore areas (He et al, ; Richa et al, ; Shan et al, ). Nevertheless, in Guanabara Bay lower richness was observed in the more polluted inner bay water (Vieira et al, ), and in the coastal region of Zhejiang area, a negative correlation between AN and bacterial alpha diversity was also detected, although it was not significant (Wang et al, ).…”
Section: Discussionmentioning
confidence: 82%
“…Previous research has shown that these primer pairs were successfully implemented for water research and outperformed other primer pairs for classical and next‐generation sequencing‐based diversity studies (Klindworth et al. ; Connelly, Baer, Cooper, Bronk, & Wawrik, ; Richert et al., ; Savio et al., ; Shan et al., ). “Fusion” primers, required for the 454‐pyrosequencing process, were designed according to the guidelines for 454 GS‐FLX+ Titanium Lib‐L sequencing and contained the Roche 454‐pyrosequencing adapters and a sample‐specific multiplex identifier (MID) sequence in between the adapter and the forward primer for sample‐specific sequence tracking (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Amplicon libraries were created using two PCR primer sets, targeting part of the bacterial and archaeal 16S ribosomal RNA (rRNA) genes, including the primer pairs S-D-Bact-0341-b-S-17 / S-D-Bact-0785-a-A-21 (covering the V3-V4 region; amplicon size of approximately 464 bp; Klindworth et al 2013) and S-D-Arch-0519-a-S-15 / S-D-Arch-1041-a-A-18 (covering the V4-V6 region; amplicon size of approximately 540 bp; Klindworth et al 2013), respectively. Previous research has shown that these primer pairs were successfully implemented for water research and outperformed other primer pairs for classical and next-generation sequencing-based diversity studies (Klindworth et al 2013;Connelly, Baer, Cooper, Bronk, & Wawrik, 2014;Richert et al, 2015;Savio et al, 2015;Shan et al, 2015). "Fusion" primers, required for the 454-pyrosequencing process, were designed according to the guidelines for 454 GS-FLX+ Titanium Lib-L sequencing and contained the Roche 454-pyrosequencing adapters and a samplespecific multiplex identifier (MID) sequence in between the adapter and the forward primer for sample-specific sequence tracking (Table S1).…”
Section: Dna Extraction Pcr Amplification and 454 Amplicon Pyrosementioning
confidence: 99%